If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -8 = 9x + (2) Reorder the terms: -8 + 7x = 9x + (2) -8 + 7x = 9x + 2 Reorder the terms: -8 + 7x = 2 + 9x Solving -8 + 7x = 2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -8 + 7x + -9x = 2 + 9x + -9x Combine like terms: 7x + -9x = -2x -8 + -2x = 2 + 9x + -9x Combine like terms: 9x + -9x = 0 -8 + -2x = 2 + 0 -8 + -2x = 2 Add '8' to each side of the equation. -8 + 8 + -2x = 2 + 8 Combine like terms: -8 + 8 = 0 0 + -2x = 2 + 8 -2x = 2 + 8 Combine like terms: 2 + 8 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| Ln(2.5x)=3 | | 13x-66=90 | | 3x+5y-7x=37findx | | y^2+2y+x^2-24=14 | | 9x+2=7x+-14 | | 10x-20=7x+10 | | 6x+56+10=180 | | 0.9/COS | | 5(3x+5)=4(3x+4)+3 | | -5(5-x)+4=3(x-1) | | (-2x)/(12x) | | 2(3x+5)=4(x-5)+2x | | -2x/12x | | 6x+3=-3x+-60 | | 4(2x-2)=3(5x-3) | | -2b+8=-15 | | -198=-18x | | 6(x-4)=3(2x-5) | | 4(3-x)-(12+x)=4 | | p+1=11 | | -6(1)+2= | | 6=-2x+64 | | -6(2)+2= | | AD/BC/AC/BD | | (1/(3x)-(2/(4x)=(3/4) | | 150=15r | | u+3.9=6.13 | | 18.99x=30 | | 2x-25+x+5=180 | | (xy-1)(xy+1)(x+3)=0 | | 3=7+b | | -6(-1)+2= |